NEPENTHES DIVERSITY AND ABUNDANCE IN FIVE HABITATS IN BRUNEI DARUSSALAM - Latiff, Nurul Amal; Sukri, Rahayu Sukmaria; Metali, Faizah (REINWARDTIA, 2014)
LATIFF, N. A., SUKRI, R. S., & METALI, F. Nepenthes diversity and abundance in five habitats in Brunei Darussalam. Reinwardtia 14(1):Â  67 â 71. -- The genus Nepenthes is known to be diverse in Bornean forests and has been recorded in Brunei Darussalam in various forest types. We aim to investigate variation in Nepenthes species richness and abundance at five forest types throughout Brunei Darussalam: open secondary, heath, peat swamp, white sand and mixed dipterocarp forests. A total of thirty-nine 5 x 5 m2 plots were set up in these forest types. Within each plot, Nepenthes species abundance was quantified, with Nepenthes voucher specimens collected and identified to determine species richness. No significant differences were detected either for Nepenthes species richness or abundance between the five forest types, despite records of Nepenthes in Brunei showing preferences for particular habitat types. We suggest that average species richness and abundance remained constant regardless of forest types in this study, but that these results would likely change if sampling intensity is increased in future studies.Â